THE QUALITY OF ASYNCHRONOUS ONLINE LEARNING ON EDMODO-BASED ENGINE ELECTRICITY SYSTEM COURSE DURING COVID-19 PANDEMIC - Erwin Komara Mindarta; Moch Harly; Sumarli Sumarli; Paryono Paryono (Erudio Journal of Educational Innovation, 2020)
The decision of the Minister of Education and Culture concerning the prevention of co-19 which suddenly made "learning at home" during the pandemic forced various parties to follow the flow so that learning could take place, one of which was online learning. Measurement of the quality of asynchronous online learning is essential to do, to get a better picture and become a guideline for making improvements. Measurement includes aspects of expert assessment and student satisfaction using survey methods. The type of data collected is the data from the expert assessment and the data from the student satisfaction survey on Edmodo. Data sources included two experts and 58 students as respondents. Data collected by distributing questionnaires. The instrument used in the form of Edmodo asynchronous online learning manuals on engine electricity courses, expert assessment questionnaires and student satisfaction survey questionnaires on Edmodo. Data in the form of numbers were analyzed using descriptive statistical analysis. The conclusion is the quality of asynchronous online learning of Edmodo-based electrical engine subjects during the co-19 pandemic at the State University of Malang in terms of expert perspectives in the "Very High" category and viewed from the satisfaction of students in the "High" category.